Political and administrative decentralization in light of the work of local governments in Iraq (قضايا سياسية, 2024)
The study of the role of political and administrative decentralization in the work of local governments in Iraq after 2005 is of importance in promoting the transition towards an effective political and administrative system that enhances democracy and achieves the aspirations of citizens at the local level. By understanding how to apply decentralization concepts, local governments can achieve inclusiveness in providing basic services and effectively enhance community participation. In a way that shows that local governments play a vital role in promoting decentralization and ensuring its application on the ground, which contributes to enhancing stability and achieving sustainable development at the local level. Identifying the challenges and opportunities that Iraq faces in this context can contribute to strengthening the role of local governments in the transition towards a more effective and comprehensive administrative system.